Efektivitas Inklusi Keuangan Syariah dalam Meningkatkan Pemberdayaan UMKM (Studi Pada BMT Dasa Tambakboyo) - Novia Yusfiyanti Laili; Rohmawati Kusumaningtias (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to determine the effectiveness of Islamic financial inclusion in Baitul Maal Wat Tamwil Dana Usaha Syariah Tambakboyo (BMT Dasa) in increasing the empowerment of MSMEs. The research method used is qualitative with a phenomenological approach. The results of this study indicate that BMT has implemented Islamic financial inclusion well. Social capital plays a role in the implementation of financial inclusion. Social capital in the form of value and trust, human capital, financial capital and physical capital. BMT has provided many facilities so that MSMEs can obtain funding and can be used to develop businesses and improve the economy as a whole. Supervision conducted by BMT Dasa has also been carried out well, but BMT does not provide training for its customers. Though the training is very important for customers, especially MSMEs.